การพัฒนาความสามารถในการรู้เท่าทันสื่อเทคโนโลยีโดยการจัดการเรียนรู้แบบปัญหาเป็นฐานร่วมกับแนวคิดหมวก 6 ใบ ของนักเรียนชั้นมัธยมศึกษาปีที่ 1 - พันธุ์เสือ, วัชรวิทย์; ผาดไธสง, พรชัย (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด; Vol 4 No 1 (2567): มกราคม – เมษายน 2567, 2023)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อพัฒนาการจัดการเรียนรู้แบบปัญหาเป็นฐานร่วมกับแนวคิดหมวก 6 ใบ ให้มีประสิทธิภาพตามเกณฑ์ 75/75 เปรียบเทียบความสามารถในการรู้เท่าทันสื่อเทคโนโลยีของนักเรียนกับเกณฑ์ร้อยละ 75 และเปรียบเทียบผลสัมฤทธิ์ทางการเรียนของนักเรียนก่อนกับหลังเรียน กลุ่มตัวอย่าง นักเรียนชั้นมัธยมศึกษาปีที่ 1 จำนวน 1 ห้องเรียน รวมทั้งสิ้น 26 คน ภาคเรียนที่ 1 ปีการศึกษา 2566 เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูลประกอบด้วย แผนการจัดการเรียนรู้จำนวน 6 แผน 12 ชั่วโมง แบบทดสอบวัดความสามารถในการรู้เท่าทันสื่อเทคโนโลยี เป็นแบบอัตนัยจำนวน 15 ข้อ และแบบทดสอบวัดผลสัมฤทธิ์ทางการเรียน ชนิดเลือกตอบจำนวน 30 ข้อ สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ค่าร้อยละ ค่าเฉลี่ย ค่าส่วนเบี่ยงเบนมาตรฐาน One Sample  t –test และ t-test (Dependent Sample)              ผลการวิจัยพบว่า 1. การจัดการเรียนรู้แบบปัญหาเป็นฐานแนวคิดหมวก 6 ใบ ของนักเรียนชั้นมัธยมศึกษาปีที่ 1 มีประสิทธิภาพ 80.61/82.82 ซึ่งสูงกว่าเกณฑ์ 75/75 ที่ตั้งไว้ 2. นักเรียนหลังได้รับการจัดการเรียนรู้แบบปัญหาเป็นฐานร่วมกับแนวคิดหมวก 6 ใบ มีความสามารถในการรู้เท่าทันสื่อเทคโนโลยีหลังเรียนสูงกว่าเกณฑ์ อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 3. นักเรียนที่ได้รับการจัดการเรียนรู้แบบปัญหาเป็นฐานร่วมกับแนวคิดหมวก 6 ใบ มีผลสัมฤทธิ์ทางการเรียนหลังเรียนสูงกว่าก่อนเรียนอย่างมีนัยสำคัญทางสถิติที่ระดับ .05              The purposes of this research were: 1) to develop Problem-Based learning with the concept of six thinking hats to be effective according to the 75/75 criterion. Comparing with the development of media literacy abilities of students according to the criteria of 75%. And to compare the learning achievement before and after. The target group of this research consisted of the   grade students in Semester 1, Academic Year 2023, with 1 classroom of 26 people. The research tools were divided into three categories including a learning management plan with 6 plans. developing the ability to be literate in the technological media test was a write-up examination and 15 items.  And a test to measure learning achievement. The kind of test was objective, and 30 items. The statistics used in data analysis are Percentage Mean Standard Deviation One Sample t–test and t-test (Dependent Sample).            The results of the research found that: 1. Problem-Based learning and the concept of six thinking hats of the   grade students effective to 80.61/82.82 which is above the threshold 75/75. 2. A student who receives Problem-Based learning and the concept of six thinking hats has the development of media literacy abilities after learning was higher than the specified criteria at statistical significance at .05 level.  3. A student who receives Problem-Based learning and the concept of six thinking hats has the learning process. The learning achievement after learning management was significantly higher than before learning management at .05 level.